2014
DOI: 10.7824/rbh.v13i2.226
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidade de plantas de café micorrizadas à herbicidas

Abstract: Resumo -Objetivou-se com esse trabalho avaliar o efeito de herbicidas aplicados em pós-emergência em plantas de café arábica inoculadas com fungos micorrízicos arbusculares. O experimento foi conduzido em esquema fatorial 2 x 6, sendo mudas de café arábica cultivar Catuaí IAC 99 inoculadas e não inoculadas com fungos micorrízicos arbusculares (Fator 1), e cinco herbicidas (chlorimuron-ethyl, oxyfluorfen, fluazifop-p-butil, fomesafen, [fluazifop-pbutil+fomesafen]) e uma testemunha (Fator 2), com quatro repetiçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In the same way, Ronchi (2003) used the herbicide Clethodim and observed selectivity of this chemical group to coffee seedlings, thus corroborating the results found in this study. Carvalho et al (2014) studied the herbicide Fluazifop-p-butyl in coffee seedlings with and without inoculation of arbuscular mycorrhizal fungi, and observed 'Catuaí IAC 99' selectivity at the herbicide package-insert dose. However, the same authors observed that, when mixed with the herbicide Fomesafen, there are growth losses in coffee plants.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, Ronchi (2003) used the herbicide Clethodim and observed selectivity of this chemical group to coffee seedlings, thus corroborating the results found in this study. Carvalho et al (2014) studied the herbicide Fluazifop-p-butyl in coffee seedlings with and without inoculation of arbuscular mycorrhizal fungi, and observed 'Catuaí IAC 99' selectivity at the herbicide package-insert dose. However, the same authors observed that, when mixed with the herbicide Fomesafen, there are growth losses in coffee plants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the contact effect of PPO-inhibitors, even if injuries occur, new leaves are not affected after application (Oliveira Junior, 2011;Silva et al, 2019), which explains the recovery of coffee plants to the application saflufenacil alone at 49 DAA The association of saflufenacil with other herbicides is necessary to increase the spectrum of weed control (Agostineto et al, 2016;Grossmann et al, 2011;Jhala;Ramirez;Singh, 2013). Although there may be antagonisms between PPO-inhibiting and ACCase-inhibiting (Rodrigues;Almeida, 2018;Rustom et al, 2019), our results showed that sethoxydim potentiated the effect of saflufenacil, when compared to the isolated application, In addition, sethoxydim with systemic translocation and action in meristematic regions, prolonged the effect of saflufenacil, configuring a harmful factor to growing coffee trees.In the same way Carvalho et al (2014), observed that coffee seedlings showed symptoms of phytotoxicity to fomesafen (PPO) mixed with flauzifop-p-buthyl (ACCase), the same effect not occurring in isolated applications of these herbicides.…”
Section: Phytotoxicity Assessmentmentioning
confidence: 79%
“…As they are young plants, the initial development stage, contributed to the resultsof the applications of saflufenacil alone and in association. Considering that plants with 2 -6 pairs of leaves are more sensitive to PPO-inhibiting herbicides, due to the greater leaf wetness and greater penetration due to the lower deposition of cuticular wax (Carvalho;Netto, 2016;Gonçalves;Carvalho, 2017). According to Oliveira Junior (2011); Silva et al (2017a), plants considered tolerant to PPO inhibitors, can present injuries, from moderate to severe, and that drift with small drops cause the appearance of small white spots on the leaves after application in post-emergence.…”
Section: Phytotoxicity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbicide effect depends on many factors, including plant physiology, environmental conditions, application conditions etc., and those factors also influence each other (CARVALHO 2013). Air temperature (an environmental condition) can affect, for example, both plant physiology and herbicide properties.…”
Section: Leonardo Bianco De Carvalhomentioning
confidence: 99%